Determinan Kejadian Obesitas Sentral pada Remaja di SMAN 4 Kota Jambi - Imelda Agustin; Marta Butar Butar; Ashar Nuzulul Putra; Adelina Fitri (Jurnal Ilmu Kesehatan dan Gizi, 2026)
Central obesity is a condition of excess fat accumulation in the intra-abdominal area, particularly in visceral tissue. This study aims to analyze the determinants of central obesity in adolescents at SMAN 4 Jambi City. This study was an observational analytical study with a cross-sectional design. The population was all active students. The study sample consisted of 172 respondents with sample selection carried out using purposive sampling. Data analysis was performed using the chi square test. The results showed that socioeconomic status [p-value=0.007; PR=2.08 (95% CI: 1.13-3.82)], physical activity [p-value=0.000; PR=1.98 (95% CI: 1.41-2.78)], consumption of risky foods [p-value=0.000; PR=3.75 (95% CI: 1.62-8.67)], vegetable/fruit consumption [p-value=0.020; PR=2.02 (95% CI: 1.02-3.99)], emotional mental disorders [p-value=0.000; PR=3.02 (95% CI: 1.97-4.62) and emotional eating [p-value=0.001; PR=1.93 (95% CI: 1.30-2.85). Factors that were not related to the incidence of central obesity in adolescents were gender [p-value=0.921; PR=0.98 (95% CI: 0.67-1.41)] and smoking status [p-value=0.195; PR=1.30 (95% CI: 0.88-1.91)]. There is a significant relationship between socioeconomic status, physical activity, consumption of risky foods, consumption of vegetables/fruits, emotional mental disorders and emotional eating with the incidence of central obesity.